1994
DOI: 10.1002/tea.3660310905
|View full text |Cite
|
Sign up to set email alerts
|

The reading–science learning–writing connection: Breakthroughs, barriers, and promises

Abstract: This article establishes a broad framework from which to interpret and evaluate the reading–science learning–writing connection. The presentation of breakthroughs, barriers, and promises is intended to outline the established links between, to identify current bottlenecks in thinking about, and to highlight productive inquiries into, print‐based languages and scientific understanding. The ideas presented come from various disciplines connected to science education. The ideas are meant to be informative, provoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
0
14

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 58 publications
1
110
0
14
Order By: Relevance
“…We subjected the measure of conceptual knowledge to an analysis of content validity. The science education professor working with the project determined that the materials available to the learner, the question, and the open-ended writing opportunity followed by the prompted response opportunities gave us a sensitive indicator of the depth of conceptual understanding about this science topic (Holliday, Alvermann, & Yore, 1994).…”
Section: Measurement Characteristics Of Constructsmentioning
confidence: 99%
“…We subjected the measure of conceptual knowledge to an analysis of content validity. The science education professor working with the project determined that the materials available to the learner, the question, and the open-ended writing opportunity followed by the prompted response opportunities gave us a sensitive indicator of the depth of conceptual understanding about this science topic (Holliday, Alvermann, & Yore, 1994).…”
Section: Measurement Characteristics Of Constructsmentioning
confidence: 99%
“…This includes more general findings on knowledge organization in expertise, the role of prior knowledge (both conceptual and cultural) in learning, and conditions that facilitate the transfer of knowledge (NRC, 2000a). It also includes specific findings on characteristics of content area text that affect comprehension and learning as well as procedures for teaching students to learn from reading texts (Alexander & Kulikowich, 1994;Holliday, Yore, & Alvermann, 1994;Hynd, McWhorter, Phares, & Suttles, 1994), and content-specific instructional strategies and representations that support student learning (Chinn & Brewer, 1993;Guzzeti, Snyder, Glass, & Gamas, 1993;Scott, Asoko, & Driver, 1992;Smith, Blakeslee, & Anderson, 1993;White & Frederiksen, 1998). These findings have implications for the design of texts and teacher's guides, and can serve as the basis for criteria to judge the quality of curriculum materials (Good & Shymansky, 1986;NRC, 1999NRC, , 2000aNRC, , 2000b.…”
mentioning
confidence: 99%
“…More specifically, Quitadamo and Kurtz (2007) in their study demonstrated that writing helps students enhance their inference skills. Writing is effective because students must not only organize their thoughts conceptually but also monitor their awareness of thinking processes (Langer & Applebee, 1987;Ackerman, 1993;Holliday, 1994;Rivard, 1994).…”
Section: International Journal Of Research Studies In Language Learnimentioning
confidence: 99%